1994
DOI: 10.1111/j.1365-2923.1994.tb02534.x
|View full text |Cite
|
Sign up to set email alerts
|

An experiment in problem-based learning

Abstract: Problem-solving skills are important for medical students and problem-based learning (PBL) is especially suited to general practice. Therefore an experiment using a form of PBL was introduced into a new 4-week course in general practice for final rotation students at the University of Glasgow in the session 1992-93. The experiment aimed to introduce students to an alternative method of learning to the traditional one previously used by them in their course, to encourage teamwork and to encourage the use of alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
0
18
0
4
Order By: Relevance
“…Other research confirms that at least some of the excess time that students associate with PBL may be directed at information gathering, and therefore suggests that it is the nature of a problem that can be fixed 44 "in a packed medical curriculum the advantages of ease of retrieval of information from textbooks and the compact presentation of facts possible in lectures are all too readily appreciated" (p.144).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Other research confirms that at least some of the excess time that students associate with PBL may be directed at information gathering, and therefore suggests that it is the nature of a problem that can be fixed 44 "in a packed medical curriculum the advantages of ease of retrieval of information from textbooks and the compact presentation of facts possible in lectures are all too readily appreciated" (p.144).…”
Section: Resultsmentioning
confidence: 93%
“…Morrison and Murray, 44 in discussing the results of a student survey of PBL course which provided evidence of high motivation but low relevance, suggest that at least some of basis for the low scores in perceived relevance could be directly related to exam anxiety, stating that Support structures need to consider the wider context in which students find themselves. The benefits of PBL are often constrained by implementation factors, such as consideration for external (non-PBL) courses and student perceptions of time requirements, or by gradual introduction of the PBL environment (such as gradated fidelity), or by bounding the degree to which ideals are attempted to be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Morrison JM stated that, it is possible to introduce problem-based learning into new curriculum parallel with traditional modes of teaching. [14]. PBL does not appear to hamper knowledge acquisition and may develop characteristics that result in "better" clinicians postgraduation.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty members have expressed doubts about the wisdom, effectiveness, and educational efficacy of such a format to teaching the sciences basic to medicine [5] Experiments by medical teachers have shown that it is possible to introduce a problem-based form of learning into a new course in parallel with more traditional modes of teaching, making it successful to some extent for students who are used to a didactic form of curriculum [6]. Our study revealed that posing problems of clinical situation to students make the inquiry driven learning more interesting.…”
Section: Discussionmentioning
confidence: 99%